KUALITAS PELAYANAN PADA PELANGGAN SPEEDY PERSEROAN TERBATAS TELKOM COSTUMER SERVICE AREA PALU - Putu Rimantari Diatmika Arya, Niluh (Katalogis, 2015)
This research aims at identifying service quality to customer of speedy incorporated company Palu and analyzing the inhibiting and supporting factors in service activity of PT.Telkom Cs area Palu. Method used in this research is descriprtive qualitative. The data were collected through observation, interview, and documentation. Six informants involved in this research were taken purposively. There are some aspect affecting the service quality according to indicator of Fitzsimmons such as 1) Reliabilty, the service conductred appropriately based on the service standar, 2) Responsiveness, the costumer did not get fast respond when they are complaining. It means that the service is not optimalazied well. 3) Assurance, the service is good particularly in showing the courtesy to the costumer. 4) Emphaty, the costumer served very well and 5) Tangible, the service is supported by facilities and good human resources. Therefore, it can be concluded that the service quality to speedy costumer of PT. Telkom CS area Palu is categorized as inadequate.